Workforce Readiness Training: A Comprehensive Training Model That Equips Community Health Workers to Work at the Top of Their Practice and Profession - Lee, Lily K.; Ruano, Elizabeth; Fernández, Pamela; Ortega, Silvia; Lucas, Carlos; Joachim-Célestin, Maud (Frontiers in Public Health, 2021)
Background: Recent reports have recognized that only 20 percent of health outcomes are attributed to clinical care. Environmental conditions, behaviors, and social determinants of health account for 80 percent of overall health outcomes. With shortages of clinical providers stressing an already burdened healthcare system, Community Health Workers (CHWs) can bridge healthcare gaps by addressing these nonmedical factors influencing health. This paper details how a comprehensive training model equips CHWs for workforce readiness so they can perform at the top of their practice and profession and deliver well-coordinated client/patient-centered care. Methods: Early literature reviews and studies revealed that training CHWs alone is not sufficient for successful workforce readiness, rather CHW integration within the workforce is needed. Consequently, this comprehensive training model is developed for CHWs with varying skill levels and work settings, and supervisors to support organizational readiness and CHW integration efforts. A systematic training program development approach along with detailed implementation methods are presented. Continuing education sessions to support CHW practice and Organizational Readiness Training for supervisors, leadership and team members directly engaged with CHWs in the workplace are also discussed. CHWs were involved in all phases of the research, development, implementation, and actively serve in evaluations and curriculum review committees. Results: Components of the comprehensive training model are presented with an emphasis on the core CHW training. Two CHW training tracks are offered using three delivery modalities. Process measures with student learning objectives, outcome measures developed using the Kirkpatrick model to capture attitude, perceptions, knowledge acquisition, confidence, behavior, and overall experience, and impact stories by two CHWs are presented. Lessons learned from the implementation of the training program are discussed in three sections: Practice-driven curriculum, student-centered training implementation, and adaptations in response to COVID-19 pandemic. Conclusion: This comprehensive training model recognizes that training CHWs in a robust training program is key as the demand for well-rounded CHWs increases. Furthermore, a comprehensive training program must include training for supervisors, leadership and team members working directly with CHWs. Such efforts strengthen the CHW practice and profession to support the delivery of well-coordinated and holistic client/patient-centered care.